Hospital unit costs in Jordan: Insights from a country facing competing health demands and striving for universal health coverage - Eman A. Hammad; Ibrahim Alabbadi; Fardos Taissir; Malek Hajjwi; Nathir M. Obeidat; Qais Alefan; Rimal Mousa (Health Economics Review, 2022)
Background: Public providers in Jordan are facing increasing health demands due to human crises. This study aimed to benchmark the unit costs of hospital services in public providers in Jordan to provide insights into the outlook for public health care costs. Methods: The unit costs of hospital services per admission, inpatient days, outpatient visits, emergency visits and surgical operations were estimated using the standard average costing method (top-down) for the fiscal year 2018- 2019. The unit costs per inpatient day were estimated for nine specialities and staff in Jordanian dinars (exchange rate JOD 1 = USD 1.41). Results: The average unit cost per admission in Jordan was JOD 782.300 (USD 1101.80), the per inpatient day cost was JOD 236.600 (USD 333.20), the per bed day cost was JOD 172.900 (USD 244.90), the per outpatient visit cost was JOD 58.400 (USD 82.30), the per operation cost was JOD 449.600 (USD 633.20) and the per emergency room visit cost was JOD 31.800 (USD 44.80). The specialities of ICU/CCU and OB/GYN presented the highest unit costs per inpatient day across providers: JOD 377.800 (USD 532.90) and JOD 362.600 (USD 510.70), respectively. The average salaried unit cost of staff depended mainly on year of employment. Nonetheless, the unit costs varied depending on the service utilization, type of service and organizational outlet. Conclusions: Knowledge of how unit costs vary across public providers in Jordan is essential to outline cost control strategies and inform future research. Institutionalization of the cost information system and high-level governmental support are necessary to generate a routine practice of collecting and sharing cost information.
Keywords: 330; Unit costs; Jordan; Healthcare Financing; Low- and middle-income countries; Hospital efficiency; Universal Health coverage